TMP21 in Alzheimer’s Disease: Molecular Mechanisms and a Potential Target - Qiu, Kaixin; Zhang, Xiaojie; Wang, Shuai; Li, Chunyan; Wang, Xin; Li, Xuezhi; Wu, Yili (Frontiers in Cellular Neuroscience, 2019)
Alzheimer ’s disease (AD) is the most common form of dementia in the elderly, which is characterized by progressive cognitive impairment. Neuritic plaques, neurofibrillary tangles and neuronal loss are the major neuropathological hallmarks in AD brains. TMP21 is a key molecule for protein trafficking in cells. Growing evidence indicated indicates that TMP21 is dysregulated in AD, which plays a pivotal role in neuritic plaque formation. Therefore, we aim to review the dysregulation of TMP21 in AD, the role of TMP21 in neuritic plaque formation and underlying mechanisms. Moreover, the potential role of TMP21 in neurofibrillary tangle formation, synaptic impairment and neuronal loss is discussed. It will provide an outlook into the potential of regulating TMP21 as a therapeutic approach for AD treatment.